ENTRE O ESPERADO E O VIVIDO: EXPECTATIVAS E EXPERIÊNCIAS DE MULHERES EM RELAÇÃO AO MOMENTO DO PARTO E NASCIMENTO - SANTOS, Alice Parentes da Silva (2017)
Introduction: Good practices towards parturition and birth are recomendations based on scientific evidence of researches performed in different countries, which are the foundation for the work of Rede Cegonha, which aims to promote humanized assistance with quality, in addition to give women the chance of having a safe and positive experience, during pregnancy, parturition and birth. Among the notable and proved practices, which must be stimulated during labor, parturition and post-parturition we shall highlight: the free will companion during labor, parturition and post-parturition; the skin-to-skin contact between mother and child and the breastfeeding as precocious practices developed, preferably, in the first hour of life of the newborn. Objectives: To analyze the expectations and experiences of women during parturition and birth. Method: Qualitative research divided in three phases: prenatal interview; the observation of parturition; interview during puerperium. For database analysis, it was used the Contest Analysis in the Theme modality. Results and discussion: Eighteen women in the prenatal phase were interviewed. Among them, twelve were interviewed during puerperium and four were observed during parturition. The categories that highlighted in the research were: Too many doctors, no bond; An individual of the family would bring us another perspective from the birth room; The kind of parturition expected and the kind of parturition experienced; Sometimes they already put on the chest. Among the practices studied, the free will companion was the nearest recommended by the good practices during parturition and birth. On the other hand, breastfeeding showed the worst results during the research. Final considerations: Despite the actions on national levels, that aim to encourage the implementation of good practices during parturition and birth, those practices still presents many challenges.